Pengaruh Stres Kerja Terhadap Kepuasan Kerja Pada Anggota Satuan Polisi Pamong Praja Di Kota Bitung - Hamisi, Yusuf (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2021)
With the vision of realizing peace, public and community protection in the implementation of development and community in the region, the Civil Service Police Unit as a regional apparatus, has a very important role in public services and to strengthen regional autonomy. Starting from general and social protection, the institutional side needs to be improved to the human resources. The purpose of this study was to examine and analyze how the influence of work stress on job satisfaction of members of the Civil Service Police Unit in Bitung City. The type of research used in this research is quantitative research. The population in this study are members of the Civil Service Police Unit in Bitung City who work in the fields of Tibum and Tramas (Public Order), the sample taken in this study is the operational section of members of the Civil Service Police Unit in Bitung City. The analytical technique used in this research is quantitative analysis technique using simple linear regression. From the results it can be said that work stress has a significant effect on work.